Answer:
f(2) = -40
Step-by-step explanation:
Just substitute x=2 into the function:
f(x) = 2x³ - 3x² - 18x - 8
f(2) = 2(2)³ - 3(2)² - 18(2) - 8
f(2) = 2(8) - 3(4) - 36 - 8
f(2) = 16 - 12 - 44
f(2) = 4 - 44
f(2) = -40
Answer:
Answer is x = -7/6
Step-by-step explanation:
please look at the image
4/8 = 1/2 so it is four eigths in one half. 4/8 simplified is 1/2
Set the equation to 0. new equation would be y^2/36 - x^2/121 = 0
factor the new equation: (y/6 + x/11)(y/6 - x/11) = 0
y/6 + x/11 = 0 —> y = -6x/11
y/6 - x/11 = 0 —> y = 6x/11
the asymptotes would be y = -6x/11, y = 6x/11